Declarive web form design for XForms in e-business applications - Gardner, W.; Chang, Elizabeth; Dillon, Tharam S. (IEEE, 2005)
In e-Business Applications, 'web form' plays an important role in providing advance interaction between the user and the system. XForms is the new web form standard recommendation by the World Wide Web Consortium (W3C) to replace the current HTML based web form implementation. In this paper, we present the notion of using Web User interaction Analysis Model (WUiAM), a proven conceptual level modelling techniques for web user interface design as a framework to support the logical design and development of XForms applications.